Unexpected ocular morphological changes after corneal refractive surgery: A review - De Bernardo, Maddalena; Pagliarulo, Sergio; Rosa, Nicola (Frontiers in Medicine, 2022)
Corneal refractive surgery (CRS) currently is widely used to correct refractive errors because of its efficacy and reliability. Several studies dealt with the corneal modification induced by this type of surgery, but it is still debated if CRS can induce unexpected changes namely anterior chamber depth (ACD) and axial length (AL). A literature review was performed, including all articles regarding CRS and eye-variations from 1999 to December 2021. Excluding articles about specific systemic conditions (e.g. pregnancy), pathological conditions, post-surgical complications or about only corneal flattening and thinning post CRS, we found nine studies that met the search criteria. We divided the found articles according to the type of surgery performed (radial keratotomy, PRK/LASEK, lasik) and analyzed the results about ACD and AL. Finally, according to the literature, we can conclude that CRS not only gives a corneal flattening, thinning and biomechanical changes, but also induces AL and ACD decrease. This makes the AL and ACD measurements obtained before CRS uselessness in case of IOL power calculation.